IMPLEMENTATION OF MODERN METHODS OF FINANCIAL SYSTEM MANAGEMENT IN ENTERPRISES OF UZBEKISTAN (World Economics and Finance Bulletin, 2025)
The current stage of economic development in Uzbekistan necessitates the introduction of innovative financial management methods at the enterprise level. This article examines contemporary approaches to financial system management, focusing on their relevance and application in Uzbek enterprises. The research employs comparative analysis, economic-statistical methods, and sectoral case studies of leading companies. The article proposes a sectorspecific model for gradual implementation of modern financial management methods adapted to Uzbekistan’s economic environment.
Keywords: financial management; digitalization; ERP systems